Implementasi Rencana Tata Ruang Wilayah dalam Upaya Pembangunan Daerah Perkotaan (Studi pada Kecamatan Kedungkandang Kota Malang) - Rizka Arlina (Jurnal Administrasi Publik, 2014)
Absract: Implementation of Spatial Regionâ€™s Plans as an Effort of the Urban Development (Studies in Kecamatan Kedungkandang, Malang City). In the implementation of the Malang Spatial Region Planningâ€™s policy (2010-2030), there is a discrepancy that development of Kedungkandang District is relativ slow. Based on the results of the study, show that the utilization of space in the Kedungkandang District based on Spatial Structure and Utilization Patterns of space as well as has been developed in accordance with the spatial regional plans. However, the infrastructure development of the transportation support systems are still not realized according to a predetermined time. So the development of â€œprotected areasâ€ (green areas) and especially, â€œcultivated areaâ€ can notÂ  be maximum developed. Supporting factors for the implementation of spatial regional planning in the Kedungkandang District is the existence of local regulations on spatial regional planning it self, the availability of undeveloped land that is quite extensive, and public participation in the planning process. However there are also things that hinder the implementation of spatial regional planning, such as topography of Kedungkandang District, the limited resources of both capital resources and personnel resources, and the mindsets of the people in certain parts of the region that can not accept the change and the development. Â  Keywords: implementation, Spatial Regionâ€™s Plan, KedungkandangDistrict Â  Abstrak: Implementasi Rencana Tata Ruang Wilayah dalam Upaya Pembangunan Daerah Perkotaan (Studi pada Kecamatan Kedungkandang Kota Malang). Dalam implementasi kebijakan Rencana Tata Ruang Wilayah Kota Malang tahun 2010-2030, terjadi ketidaksesuaian yaitu perkembangan Kecamatan Kedungkandang yang relativ lambat. Berdasarkan hasil penelitian, pemanfaatan ruang di wilayah Kecamatan Kedungkandang berdasarkan Struktur Ruang dan Pola Pemanfaatan ruang telah berkembang sesuai dengan RTRW. Namun, pembangunan infrastruktur sistem penunjang transportasi masih belum terealisasi sesuai waktu yang telah ditentukan. Sehingga pembangunan kawasan lindung dan khususnya kawasan budidaya belum bisa terbangun secara maksimal. Faktor pendukung dari implementasi RTRW di Kecamatan Kedungkandang adalah adanya peraturan daerah tentang RTRW itu sendiri, ketersediaan lahan belum terbangun yang cukup luas, dan partisipasi masyarakat dalam proses perencanaan. Walaupun begitu juga terdapat hal yang menghambat dalam implementasi RTRW, seperti kondisi topografi wilayah di Kecamatan Kedungkandang, keterbatasan sumber daya baik sumber daya modal maupun sumber daya aparatur, dan pola pikir masyarakat di bagian wilayah tertentu yang belum bisa menerima adanya perubahan dan pembangunan. Â  Kata Kunci : implementasi, Rencana Tata Ruang Wilayah, Kecamatan KedungkandangÂ